Quick septoplasty in children: Long-term effects on nasal breathing and dentofacial morphology. A prospective cephalometric study. Issue 5 (October 2021) - Ori, Michele; Ricci, Giampietro; Capalbo, Maria; Maranzano, Massimo; Sarno, Antonio; Di Stadio, Arianna; D'Ascanio, Luca
Abstract: Objective: Many authors have investigated the most appropriate surgical approach to the deviated septum in childhood, considering the obligate mouth-breathing habit a possible cause of malocclusion and disharmonious development of the facial skeleton in growing kids. Nevertheless, controversies still remain about the long-term functional/esthetic results of such procedures, mainly due to the duration of the follow-up and possible confounding factors. Methods: 111 Caucasian children (age range: 6–13 years) were submitted to a personal "Quick" septoplasty surgical technique between 2005 and 2010. Preoperative otorhinolaryngological examination using flexible nasal endoscopy, anterior active rhinomanometry (AAR), Nasal Obstruction Septoplasty Effectiveness (NOSE) questionnaire, and dentofacial evaluation (including cephalometry) were performed. Postoperative AAR, NOSE questionnaire and cephalometric assessment were carried out in all patients at the age of 18 years. Informed consent was obtained from children's parents as appropriate. Results: No surgical complication was recorded. Among our patients, a significant ( p  <0.001) improvement of nasal breathing resistances at AAR and NOSE questionnaire scores was found after surgery. A significant improvement in cephalometric/dental parameters (gonial angle values, anterior facial height, prevalence of class I occlusion, maxillary intermolar width, and cross-bite frequency) was noticed after the follow-up with respect to preoperative conditions. Conclusion: The "Quick" septoplasty technique described is a practical and conservative procedure with a low complication rate that offers long-term favourable results for the correction of nasal septum deviations in children. Nasal-breathing restoration may favor a physiological and harmonious development of craniofacial and dental structures in offspring.